1987
DOI: 10.1136/bmj.294.6580.1133
|View full text |Cite
|
Sign up to set email alerts
|

Use of the automatic external defibrillator-pacemaker by ambulance personnel: the Stockport experience.

Abstract: In an attempt to reduce the number of people who die from a cardiac arrest in the Stockport area ambulances were equipped with automatic external defibrillator-pacemakers, and ambulance personnel were trained in their use. Over an 18 month period ambulance personnel attended 113 patients in cardiac arrest with these devices. One patient subsequently survived, and three patients survived for up to three days.The reasons for these poor initial results include the failure of bystanders to provide cardiopulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Of the 1-year survivors, 86% were in the best Cerebral Performance Category Scale class, 1 and there were no cases of class 4 vegetative state or class 5 brain death (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 1-year survivors, 86% were in the best Cerebral Performance Category Scale class, 1 and there were no cases of class 4 vegetative state or class 5 brain death (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, survival to hospital discharge remains poor, with survival rates for all rhythms combined ranging from 1% to 20%. 1,2 Variation in survival rates among communities can be attributed to differences in the chain of survival concept, as described by the American Heart Association. 3,4 It is generally believed that the best survival can only be achieved if all 4 of the following links have been optimized: (1) rapid access, (2) early cardiopulmonary resuscitation, (3) early defibrillation, and (4) early advanced cardiac life support.…”
mentioning
confidence: 99%
“…EMTs and paramedics were the first to deploy AEDs in OHCA safely and effectively [54][55][56]. Documentation of improved survival following automated defibrillation by EMTs soon followed [57][58][59][60]. Two meta-analyses [61,62] demonstrated that defibrillation by basic life support providers reduced the relative risk for death for a person experiencing OHCA with ventricular fibrillation.…”
Section: Within the Traditional Health Care Systemmentioning
confidence: 95%
“…Despite these early initiatives in Brighton there was little progress elsewhere in the UK with these devices during the 1980s. Chapman and Chamberlain (1987) reported that they were training aircraft cabin crew to use them and Gray, Redmond and Martin (1987) equipped ambulances in Stockport with them, but reported very poor results with regard to survival.…”
Section: 13mentioning
confidence: 99%